The impact of mobility and migration in the Roman empire : proceedings of the twelfth workshop of the International Network Impact of Empire (Rome, June 17-19, 2015) - Impact of Empire (Organization) (2016)
Following on previous workshops of the Impact of Empire network which looked at frontiers (Impact 9), integration (Impact 10) and the world(s) beyond the borders of the Roman empire (Impact 11), the twelfth meeting of the network focused on movement within the Roman world. The Impact of Mobility and Migration in the Roman Empire assembles a series of papers on key themes in the study of Roman mobility and migration. It discusses legal frameworks, the mobility of the army (both at war and in peace-time), ethnic identity, the mobility of women, the mobility of senators, diplomatic mobility, war-induced mobility, and deportations. The papers vary in geographical scope, ranging from empire-wide approaches to reconstructions of patterns at particular sites. It employs a rich variety of sources, ranging from classical authors to documentary papyri, from legal sources to shipwrecks.